Castle Butte - Nesbitt, John D. (Five Star, a part of Gale Cengage Learning, 2018)
In 1890s Wyoming, seventeen-year-old Alden Clare assumes the responsibility of earning enough money to buy back his family's foreclosed land, taking care of his older brother's family, and helping the attractive daughter of a homesteader who is being harrassed by ruffians.